Sacral Geography as a System: Problem of Sacral Object’s Status - A. P. Lipatova (Научный диалог)
The author proposes to consider the revered loci of a particular area as a system, the elements of which are not isolated from each other, but demonstrate the relationship. The article hypothesizes that the connection between elements within the system of sacred loci of a certain territory is not only manifested at the level of the actional code of objects veneration, but is also expressed in the etiological texts explaining the special status of loci. The information fund of the officially recognized sacral center - a kind of system’s unique - demonstrates the connection with the information fund of sacral periphery - springs, the popularity of which does not go beyond one or two villages. Particular attention is paid to the analysis of texts with the plot motive “icon’s leaving.” The motive of a sacral object’s leaving allows to link the history of somebody’s own village with the history of a sacral center, to join the positive assessment of the well-known locus, its centuries-old history. This helps to improve the status of unpopular objects. The cultural landscape is seen as a system, not as a fragmented collection of elements. It is argued that without a painstaking analysis of an object’s status the adequate perception of folklore stories about it is impossible.